Exploration of Predictive Models for Lean Services in Government Lean Banking Industry - Fazel Saydi; Morteza Musa Khani; Sedigheh Tootian; Shahrazad Tayaran (‫مدیریت بازرگانی)
ObjectiveBased on macroeconomic indicators, a significant portion of the world's gross domestic product comes from the services sector. The $2.7 trillion share of services in large economies and its increasing growth since 2011, according to UN accounts, highlight the undeniable importance of the services sector. In line with this perspective, previous researchers have shown that lean-based approaches can facilitate the efficient and development-oriented growth of the services sector. Producers' move towards lean-based strategies in services has been reported to exceed 30%, a significant factor in maintaining competitiveness and gaining a competitive advantage in the service industry. The concept of lean first emerged in the industry with a focus on eliminating waste from production and refining it. However, this concept has entered the theoretical literature of organizations on the one hand, and on the other hand, it has appeared in the public domain, such as public administration and governance. Therefore, concepts such as lean government and lean services are outcomes of this concept. The present study aims to identify and validate a predictive model of lean services in the context of lean government in the banking industry. MethodologyIn terms of paradigm, this research is interpretive during the model discovery phase and confirmatory during the model testing phase, and it is generally pragmatic. The research sample for the qualitative phase consists of experts in the academic field, including university professors, faculty members, and banking industry managers. A total of 15 experts were interviewed to collect qualitative data. The research questionnaire was developed based on exploratory factor analysis to collect quantitative data. In the quantitative section, using G*Power sample size determination software with an alpha level of 0.01 and a power test of 85%, 190 individuals were selected as the final sample for the research. The research approach is mixed, and the strategy employed is thematic analysis. Clark's method (2006) was used to analyze the data with MAXQDA software. The path analysis of the discovered model was also examined using variance-based structural equation modeling algorithms with SPSS version 24 and SmartPLS version 3. FindingsThe results of the data analysis show that 32 indicators and 7 variables in the context of 6 theories were identified and validated as predictors of lean services for the realization of lean government in the Iranian banking industry. Therefore, factors such as lean improvement strategy, lean cultural transformation, development of lean capabilities, lean management methods, lean work methods, and lean contextual factors can facilitate the realization of lean services. ConclusionThe banking industry is one of the driving forces of the economy and the engine of every society. Therefore, paying attention to the banking sector and its growth and development is an inevitable necessity. In particular, in the field of banking services, this is important due to the nature of financial and monetary services. Economic liberalization, globalization, and increasing competitiveness in financial services have forced banks to enhance and expand their services to maintain a competitive position. In the present study, the predictive theories of lean services with a lean government approach in the Iranian banking industry were identified through exploratory research, based on the natural conditions of Iranian society. Also, a conceptual model of predictors and a model for the application of lean services to the Iranian banking industry were introduced.